EXPLORING INQUIRY-BASED LEARNING IN IMPROVING READING-VIEWING SKILLS. (A CASE STUDY IN CLASS SEVENTH GRADE STUDENTS’ OF SMPN 20 KOTA BENGKULU) - Ayu Yeri Andira; Ferri Susanto; Anita (Journal of Innovative and Creativity, 2026)
This study provides an in-depth description of how the implementation of the Inquiry-Based Learning model improves the reading–viewing skills of seventh-grade students at SMPN 20 Kota Bengkulu. Using a qualitative approach with a case study design, the research subjects consisted of 30 seventh-grade students and three English teachers as primary informants. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman & Saldana model, namely data reduction, data display, and drawing/verifying conclusions. The results show that the consistent implementation of Inquiry-Based Learning increases student engagement and reading–viewing abilities. Students become more active in asking questions, are able to analyze information from texts and visual media, and present findings logically. Teachers also applied differentiation through grouping by learning styles, the use of audiovisual media, and staged guidance as facilitators. Thus, this study concludes that Inquiry-Based Learning has a positive and effective impact on improving the reading–viewing skills of seventh-grade students at SMPN 20 Kota Bengkulu, especially through analytical, collaborative, and reflective activities that are relevant to 21st-century learning needs.